MMP3 in Severe COVID-19: A Biomarker or Therapeutic Target? - Almuntashiri, Sultan; Zhang, Duo; Somanath, Payaningal R.; Sikora, Andrea (Infectious Disorders - Drug Targets, 2023)
Identifying novel therapies is a critical need in the treatment of coronavirus disease-19 (COVID-19) and acute respiratory distress syndrome (ARDS). Stromelysin-1, also known as matrixmetalloproteinase 3 (MMP3), has been investigated as a diagnostic biomarker and a potential pharmacological target. Here, we discuss the recent findings of Gelzo et al. in the context of additional MMP3 investigations to delineate its exact role in diagnosis, prognostication, and phenotyping, in addition to its promising role as a therapeutic target in COVID-19-associated respiratory failure.
Keywords: ARDS